Variability in morphological traits of seedlings from five Euonymus japonicus cultivars - Yucedag, Cengiz; Özel, Halil Barış; Cetin, Mehmet; Sevik, Hakan (Springer Science and Business Media LLC, 2019)
In this study, we investigated the variability in morphological traits of seedlings from five Euonymus japonicus cultivars. We measured seedling heights, root collar diameters, leaf lengths and widths, root lengths, root numbers, and twig numbers of 60 seedlings from each cultivar. The E. japonicus cultivars Variegate and Green Rocket had the highest (95.8%) and lowest (70.3%) rooting percentages, respectively. With the exception of root lengths (p > 0.05), all morphological characteristics significantly differed among all cultivars (p < 0.05). In particular, the cultivar Green Rocket performed better than all other cultivars, with greater seedling heights and root collar diameters. These data warrant further studies for quantifying differences in traits among these cultivars.
Keywords: Plant Leaves; Ornamental Plant; Seedlings; Euonymus Japonicus; Euonymus; Morphological Traits; Management, Monitoring, Policy and Law; Variability; Plant Roots; Landscape Design